Charge dynamics in tumbling mills : simulation and measurements with an in-mill sensor - Alatalo, Johanna (Luleå tekniska universitet, Industriell miljö- och processteknik, 2011)
Grinding is a process of reducing the particle size distribution of an extracted ore commonly performed in tumbling mills. The process is complex with many factors affecting the result, predominately the ores physical and chemical properties. The ore feed to a concentrator varies and optimisation is important, since grinding has high energy consumption and therefore is an expensive process. In an attempt to increase the knowledge of pebble mill grinding, experiments were performed with a pilot-scale mill at the LKAB R&D facilities at Malmberget. The purposes of the experiments were to investigate how the mill reacts to changes in the system and to find out how the grinding ability is affected by the changes. The first set of experiments concentrated on different operational settings, varying the filling degree, the volume-% solids and the percentage of critical speed of the mill. In the second set of experiments, different pebbles mixtures with varying magnetite content and different size fractions were tested. An interesting response variable (result) is the product size for the different operational conditions, since higher amount of fine material < 45 μm can be seen as a probable increase of production rate. The environment inside a mill is too harsh for direct measurements and there is a lack of knowledge of the events occurring inside the mill. Information on the events in the charge can be achieved by the use of different sensors. In the experiments, a Continuous Charge Measurement (CCM) system by Metso Minerals has been used to learn more about the charge dynamics. This system consists of a strain gauge detector embedded in one rubber lifter and measures the deflection as the lifter passes through the charge in the mill. The information received from the deflection curve is used in the evaluation of the experiments. The data from the experiments have been analysed with the aid of a statistical program. The analyses show that there will be an increased production of fines at low critical speed ...